EKSPLOITASI SUMBER DAYA ALAM SEBAGAI TEMA LUKISAN KACA - Prayudhi, Erik Rifky (ATRAT: Jurnal Seni Rupa, 2019)
Exploitation Of Natural Resources As A Glass Painting Theme A writing of artworks that deals with industry-caused environmental problems and impacts social problems, namely the exploitation of natural resources. With a variety of complex sources and problem factors, dealing with the ideology of capitalism to affect consumerism is a complex form of problem. This work is visualized into glass paintings using idiom forms and objects of industrial mining, buildings, machinery and animal figures also devil in the form of wayang. The author hopes to have a positive impact through the work of glass painting and to inspire, give awareness, or cultivate the feelings of the appreciators or the community. But the author also hopes to open apresiator mind with his work to be aware of environmental and social problems in the community.Â Keywords: Exploitation Natural Resources, Industrial Objects, Consumerism, Wayang Figures________________________________________________________________Â Sebuah penciptaan karya seni yang membahas permasalah lingkungan yang disebabkan industri dan berdampak kepada permasalahan sosial, yaitu eksploitasi sumber daya alam. Dengan berbagai sumber dan faktor masalah yang rumit, berhubungan dengan faham kapitalisme sampai berdampak menjadi faham konsumerisme adalah sebuah bentuk masalah yang kompleks. Karya ini divisualisasikan ke dalam lukisan kaca dengan memakai idiom-idiom bentuk dan objek industrial pertambangan, bangunan, permesinan dan tokoh-tokoh binatang serta siluman berupa wayang dengan menggunakan teknik seni lukis kaca.Kata Kunci: Eksploitasi Sumber Daya Alam, Objek Industrial, Konsumerisme, Tokoh Wayang